On Cylindrical Elastic-Plastic Shells with Moderately Large Rotations - Sławianowska, A. (Engineering Transactions, 1998)
An application of a moderate rotations theory (MRT) to cylindrical elastic-plastic shells is presented. Geometrical and kinematical relations for cylindrical shells with arbitrary cross-section are derived. Following the general procedure formulated in [4] we derive also equilibrium equations for cylindrical shells. Some special cases of loading and cross-section shapes of shells are discussed in more details. Orthotropic elastic-plastic constitutive relations are assumed and expressed in terms of a cylindrical reference frame. In a forthcoming paper we are going to apply these results as a basis for numerical solving of geometrically nonlinear problems for cylindrical shells.